Hubungan Intensitas Penggunaan Media Sosial dengan Kemampuan Menulis Akademik Mahasiswa PBSI Universitas Muhammadiyah Jember - Muhammad Hardika Ardiansyah; Muhammad Amin Amirullah; Agus Milu Susetyo (Jurnal Ilmu Bahasa dan Pendidikan Guru Sekolah Dasar, 2026)
This study aims to examine the relationship between the intensity of social media use and academic writing ability of students in the Indonesian Language and Literature Education Program at Universitas Muhammadiyah Jember. This research employed a quantitative approach with a correlational design. The research sample consisted of 49 students selected using proportional sampling techniques. Data were collected through questionnaires measuring the intensity of social media use and instruments assessing academic writing ability using a Likert scale. Data analysis was conducted using descriptive statistics and Pearson correlation with the assistance of SPSS software. The results indicate that students’ social media usage intensity falls into a high category, while their academic writing ability is classified as moderate to good. The Pearson correlation analysis revealed a correlation coefficient of r = 0.731 with a significance value of 0.000 < 0.05. These findings demonstrate a positive and significant relationship between the intensity of social media use and students’ academic writing ability. Therefore, it can be concluded that social media, when utilized in a positive and academic-oriented manner, can support the development of students’ academic writing skills.